2016
DOI: 10.1080/08977194.2016.1191480
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia suppresses myocardial survival pathway through HIF-1α-IGFBP-3-dependent signaling and enhances cardiomyocyte autophagic and apoptotic effects mainly via FoxO3a-induced BNIP3 expression

Abstract: The HIF-1α transcriptional factor and the BH-3 only protein BNIP3 are known to play fundamental roles in response to hypoxia. The objective of this research is to investigate the molecular mechanisms and the correlation of HIF-1α, BNIP3 and IGFBP-3 in hypoxia-induced cardiomyocytes injuries. Heart-derived H9c2 cells and neonatal rat ventricular myocytes (NRVMs) were incubated in normoxic or hypoxic conditions. Hypoxia increased HIF-1α expression and activated the downstream BNIP3 and IGFBP-3 thereby triggered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 46 publications
6
43
0
1
Order By: Relevance
“…We found that high glucose plus hypoxia enhanced the nuclear translocation of HIF‐1α and FoxO3a. This is consistent with our previous study, where we showed that prolonged hypoxia promoted not only HIF‐1α but also FoxO3a nuclear translocation (Feng et al, ). Third, we found that inhibition of HIF‐1α using inhibitor significantly suppressed BNIP3 expression under hypoxia plus high glucose condition, which was correlated with HIF‐1α expression (Figure a).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that high glucose plus hypoxia enhanced the nuclear translocation of HIF‐1α and FoxO3a. This is consistent with our previous study, where we showed that prolonged hypoxia promoted not only HIF‐1α but also FoxO3a nuclear translocation (Feng et al, ). Third, we found that inhibition of HIF‐1α using inhibitor significantly suppressed BNIP3 expression under hypoxia plus high glucose condition, which was correlated with HIF‐1α expression (Figure a).…”
Section: Discussionsupporting
confidence: 94%
“…It has been known that hypoxia and acidosis activate cardiac myocyte death through the Bcl‐2 family protein BNIP3 (Kubasiak, Hernandez, Bishopric, & Webster, ). We previously demonstrated that hypoxia suppressed myocardial cell survival through HIF‐1α—IGFBP‐3‐dependent signaling pathway and enhanced cardiomyocyte autophagic and apoptotic effects mainly via FoxO3a‐induced BNIP3 expression (Feng et al, ). This study focused on whether HIF‐1α, FoxO3a, and BNIP3 were also involved in hypoxic heart under elevated glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous investigations have reported that HIF-1α or FOXO3 are involved in BNIP3 expression under hypoxia [33], [34], their roles in BNIP3 expression seem to vary with cell type [35], [36], [37]. To demonstrate the detailed mechanism regulating BNIP3 expression in UCB-hMSCs under hypoxia, we investigated the roles of HIF-1α and FOXO3 in BNIP3 regulation.…”
Section: Resultsmentioning
confidence: 97%
“…BNIP3 then forms a stable homodimer complex that is inserted into the mitochondrial membrane, causing mitochondrial damage and triggering mitochondrion-dependent apoptosis [6]. Earlier reports suggested that BNIP3 plays a pivotal role in the loss of skeletal muscle mass and provides a potential therapeutic target in muscle wasting disorders and other diseases that involve autophagy [7].…”
Section: Introductionmentioning
confidence: 99%